Effects of thinning on ecosystem carbon storage and tree-shrub-herb diversity of a low-quality secondary forest in NE China - Zhang, Baoshan; Dong, Xibin; Qu, Hangfeng; Gao, Ran; Mao, Liangliang (Journal of forestry research, 2023)
Thinning is a widely used forest management tool but systematic research has not been carried out to verify its effects on carbon storage and plant diversity at the ecosystem level. In this study, the effect of thinning was assessed across seven thinning intensities (0, 10, 15, 20, 25, 30 and 35%) in a low-quality secondary forest in NE China over a ten-year period. Thinning affected the carbon storage of trees, and shrub, herb, and soil layers ( P < 0.05). It first increased and then decreased as thinning intensity increased, reaching its maximum at 30% thinning. Carbon storage of the soil accounted for more than 64% of the total carbon stored in the ecosystem. It was highest in the upper 20-cm soil layer. Thinning increased tree species diversity while decreasing shrub and herb diversities ( P < 0.05). Redundancy analysis and a correlation heat map showed that carbon storage of tree and shrub layers was positively correlated with tree diversity but negatively with herb diversity, indicating that the increase in tree diversity increased the carbon storage of natural forest ecosystems. Although thinning decreased shrub and herb diversities, it increased the carbon storage of the overall ecosystem and tree species diversity of secondary forest. Maximum carbon storage and the highest tree diversity were observed at a thinning intensity of 30%. This study provides evidence for the ecological management of natural and secondary forests and improvement of ecosystem carbon sinks and biodiversity.